Remoção de poluentes ambientais em águas residuárias: revisão bibliográfica - Santos, Anderson (Universidade Federal de São Carlos, 2025)
Concern about water supply is a topic that is highlighted by international agencies such as the UN, and water quality has been discussed mainly in terms of its potability in relation to emerging pollutants that can be found dissolved in it. Emerging pollutants are substances that have been identified in various places, such as wastewater, and do not have analysis protocols and concentration limits regulated by government agencies. As these pollutants are not regulated, they can persist in conventional water and sewage treatment processes and can cause severe impacts on the ecosystem during their disposal. With this in mind, this work presents a perspective on methods that can degrade the pesticide methomyl, an emerging pollutant that can be found in wastewater and has toxic effects on humans and aquatic life in general. Studies using Advanced Oxidative Processes (AOPs) have shown a promising alternative for the degradation of emerging pollutants, so a literature review was carried out of different AOPs that could possibly be used at scale for the degradation of methomyl. The review was based on microbiological degradation, the Fenton process, the photo-Fenton process, ozonization, photocatalysis and photo-electrocatalysis.
Removal of environmental pollutants in wastewater: bibliographical review
Keywords: Processo oxidativo avançado; Metomil; Degradação; CIENCIAS EXATAS E DA TERRA::QUIMICA